Pengaruh Program Magang dan Studi Independen Bersertifikat (MSIB) terhadap Kesiapan Kerja Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang - Salsabilla, Khoirunisa; Abidin, Zainal; Utamidewi, Wahyu (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of the Certified Internship and Independent Study Program (MSIB) on the work readiness of students in the Faculty of Social and Political Sciences at Universitas Singaperbangsa Karawang. A quantitative method was used by distributing questionnaires to 92 respondents who had participated in the MSIB program. The coefficient of determination test showed that the MSIB program contributed 37.3% to students’ work readiness. Partial tests indicated that the variables Work Skills (t = 3.650, sig. 0.001) and Attitude Formation (t = 2.706, sig. 0.008) had a significant influence, while Internship Duration (t = 1.423, sig. 0.158), Human Resource Development (t = 0.638, sig. 0.526), and Learning Outcomes Reinforcement (t = 0.265, sig. 0.791) did not show a significant effect. These results indicate that work skills such as task completion, teamwork, and operational tool usage and professional attitudes like discipline, responsibility, and initiative are key factors affecting students' work readiness. On the other hand, the insignificance of the other three variables suggests the need for evaluation of program implementation, particularly in the quality of training, mentoring, and integration of academic theory with practical application. These findings affirm that the success of the MSIB program is not solely determined by student participation, but by how such experiences shape professional competencies and attitudes aligned with workplace demands.